1978
DOI: 10.1088/0031-8949/18/3/007
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Fluctuations in Semi-infinite Plasmas

Abstract: In Section 1 of the present paper we obtain the kinetic Enhanced fluctuations in semi-infinite plasmas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…It should be noted that Rytov's approach to describe electromagnetic fluctuations, which we used here, is not unique, but one of the possible ways to calculate spectral and correlation properties based on Maxwell's equations and the fluctuation-dissipation theorem. Other examples in the case of plasma-like half-spaces, including nonequilibrium states and nonlocal effects are described, for example, in [29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that Rytov's approach to describe electromagnetic fluctuations, which we used here, is not unique, but one of the possible ways to calculate spectral and correlation properties based on Maxwell's equations and the fluctuation-dissipation theorem. Other examples in the case of plasma-like half-spaces, including nonequilibrium states and nonlocal effects are described, for example, in [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Another very interesting fact is that the larger the temperature, the smaller the relative contribution from the evanescent part to the total fields [23]. Using equations (28) and (29) it was demonstrated that…”
Section: Energy Density Of Thermal Electromagnetic Fields Of a Half-s...mentioning
confidence: 99%
“…[1][2][3][4] It is natural, that in both cases, particle collisions lead to the growth of the instability thresholds and considerably influence the instability domains.…”
Section: -9mentioning
confidence: 99%
“…Note that the imaginary part of w(k) should be neglected due to oddness of integrand (12). Then the spectral intensity of beam energy losses in unit time takes the form…”
Section: Spontaneous and Stimulated Radiation Of An Electron Beam In ...mentioning
confidence: 99%